THE EFFECT OF CULTURAL CONTACT ON REVISIT INTENTION ON YOGYAKARTA PALACE TOUR (Ekspektra : Jurnal Bisnis dan Manajemen, 2022)
This study aims to determine the effect of Cultural Contact on Revisit Intention on Yogyakarta Palace tourism. The dependent variable used is revisit intention, while the independent variables used are cultural contact, and cultural memory. The research method used is causal research with Structural Equation Modeling (SEM) approach. The research sample was 105 tourists from the Yogyakarta Palace. Data collection techniques by distributing online questionnaires. The data analysis technique used classical assumption test, Structural Equation Modeling (SEM) analysis, and hypothesis testing.